Assessment of acid sulfate soil using hyperspectral data in South Yunderup, Western Australia - Shi, X.; Aspandiar, Mehrooz; Lau, I. (2013)
Acid sulphate soils (ASS) are harmful to the environment, but it is detectable because they contain secondary iron bearing minerals which have diagnostic spectral features in reflectance spectral ranges, and these iron bearing minerals have indicative nature to reflect the pH conditions when they form, thus make ASS assessable via hyperspectral sensing. The extent and severity of ASS were mapped on the airborne remotely sensed imagery HyMap based on the mapping of indicative iron bearing minerals and the utilizing the relationship between these minerals and soil pHs. While, the distribution of ASS in subsurface was estimated by proximal hyperspectral instrument Hylogger™ and soil coring. Therefore, a comprehensive assessment of ASS both on the surface and in the subsurface was acquired and could be useful to further predict and monitor the ASS evolution. © 2013 IEEE.